2010
DOI: 10.1186/1471-2318-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of covariation in socioeconomic predictors of physical functioning and psychological well-being among older people in rural Vietnam

Abstract: BackgroundThere remains a lack of research on co-variation of multiple health outcomes and their socio-economic co-patterning, especially among the elderly. This papers aims to 1) examine the effects of different socio-economic factors on physical functioning and psychological well-being among older adults in a rural community in northern Vietnam; and 2) investigate the extent to which the two outcomes variables co-vary within individuals.MethodsWe analyzed the data from the WHO/INDEPTH study on global ageing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…Multimorbidity was significantly less common among literate people even adjusting for other variables showing that it is an independent factor and one that would be important to target in the preventative space. Studies conducted in Northern Vietnam [ 5 , 7 , 24 ] and other developing countries [ 16 , 21 ] indicated that people with better education have less risk of chronic diseases. Education empowers an individual with knowledge and skill thus educated people can be more able to access health promotion information, and adopt healthy lifestyle [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity was significantly less common among literate people even adjusting for other variables showing that it is an independent factor and one that would be important to target in the preventative space. Studies conducted in Northern Vietnam [ 5 , 7 , 24 ] and other developing countries [ 16 , 21 ] indicated that people with better education have less risk of chronic diseases. Education empowers an individual with knowledge and skill thus educated people can be more able to access health promotion information, and adopt healthy lifestyle [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on gender differences in health and disability are of considerable interest to researchers and policy makers, and a number of studies have been conducted on these issues in different settings [11, 1420]. Previous studies found several socio-demographic variables, including gender, that are associated with disability [11, 12, 14, 2027].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found several socio-demographic variables, including gender, that are associated with disability [11, 12, 14, 2027]. Older adults with multiple chronic diseases, poor self-assessed health conditions, and who practice sedentary life styles had high prevalence of functional disability [28].…”
Section: Introductionmentioning
confidence: 99%
“…16 Hoang et al (2010) document, for instance, how living alone may jeopardize both the physical and the psychological situations of the elderly after controlling for the effect of other socioeconomic and demographic factors. Poverty is indeed more frequent among elder women living alone (World Bank 2011).…”
Section: Widowhood and Isolationmentioning
confidence: 99%